Una nueva especie de Pleurothallis (Pleurothallidinae) subsección Macrophyllae-Fasciculatae para la región Andina colombiana - Sierra-Ariza, Mario Alexei (2022)
A new species of Pleurothallis that belongs to the Macrophyllae-Fasciculatae from the Colombian Andes region is described and illustrated. The new species is morphologically similarto Pleurothallis callosa from which it can be differentiated by having its dorsal sepal and synsepal ovate-elliptic; petals falcate-lanceolate, acuminate, and the lip quadrangular-ovate with 2 basal calli that extend up to a third the length of the lip (vs. dorsal sepal elliptic and synsepal widely ovate and unguiculate lip with two basal calli that extend up to half the length of the lip in P. callosa). Geographic information, ecological characteristics, and conservation status of the new species are provided.